THE IMPACT OF INNOVATION, BRAND IMAGE, AND SOCIAL MEDIA MARKETING ON MENANTEA PURCHASE INTENTION - Frandi, Toni; Ongky Alex Sander1; Soesilo, Ferdinandus; Riza, Fahrul; Sidarta, Eric (International Journal of Application on Economics and Business, 2023)
The rapid advancement of technologies and information has required companies to be more careful and thorough in the business competition especially in the food and beverage industry. As the industry is getting more competitive, companies should focus more on innovation, brand image and social media marketing to attract more customers buying their products. Few studies have explored the factors that influence consumer’s intention to buy products from small-medium enterprise in Indonesia. Small-medium enterprise should consider the factors such as brand image and social media marketing that may influence consumer’s purchase intention. This study attempts to establish a framework of factors affecting consumer’s intention on buying products of food and beverage from small-medium enterprise in Indonesia called Menantea. Several independent variables in this research are innovation, brand image and social media marketing. And the dependent variable is purchase intention. This research focuses on investigating the impact of innovation, brand image and social media marketing on consumer’s purchase intention on Menantea. This research was conducted on Menantea customers in Indonesia. The sampling method used non-probability sampling with a sampling size of 124 samples. The data was collected by the means of questionnaire. This type of research is quantitative and uses the SPSS 25. The results showed that brand image has a significant positive impact on consumer’s purchase intention on Menantea, social media marketing has a significant positive impact on consumer’s purchase intention on Menantea and innovation has no significant positive impact on consumer’s purchase intention on Menantea.